Pengaruh Debt to Equity Ratio, dan Return on Asset, Serta Return on Equity Terhadap Harga Saham PT. Unilever Indonesia Tbk Yang Terdaftar Pada Bursa Efek Indonesia Periode 2015-2022 - Komang, Tria Wahyuni; Suwendra, I Wayan (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This research was conducted with the aim of determining how the effect of debt-to-equity ratio, return on assets, and return on equity on the share price of PT. Unilever Indonesia Tbk for the period 2015-2022 is partially or simultaneously. The design used in this study is causal associative. The subject in this study was PT. Unilever Indonesia Tbk, and the objects of research are the debt-to-equity ratio, return on assets, return on equity, and share prices. The data used are secondary data analyzed by testing classical assumptions and multiple linear regression analysis. The results showed that a partially debt-to-equity ratio has a negative effect on stock prices with a significant value of 0.000 < 0.05, return on assets has a negative effect on stock prices with a significant value of 0.035 < 0.05, and return on equity has a positive effect on stock prices with a significant value of 0.001 < 0.05. Simultaneously, debt-to-equity ratio, return on assets, and return on equity have a significant effect on stock prices.